Anesthetic management of a parturient with Eisenmenger’s syndrome: A case report (Indian Journal of Case Reports, 2021)
Eisenmenger’s syndrome results from certain uncorrected congenital abnormalities of the heart facilitating left to right shunt and chronic volume overload of the pulmonary vasculature, leading to irreversible changes in the pulmonary vasculature. Pregnancy in the patients of this syndrome is associated with a high risk of cardiovascular decompensation, thromboembolic complications, and sudden cardiac death. We present the case of a 25-year-old pregnant woman with Eisenmenger’s syndrome who delivered through the vaginal route at 37 weeks of gestation, under labor epidural anesthesia. A healthy male baby was delivered within 40 min of drug deposition in the epidural space. The postpartum period was essentially uneventful with successful maternal and neonatal outcomes.